1993
DOI: 10.1093/cvr/27.8.1421
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock proteins in the normal and stunned porcine myocardium

Abstract: The findings support the hypothesis that molecular damage occurs in stunned myocardium; however, the target molecules remain to be recognised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…The decrease in SR Ca 2÷ uptake rate usually appears after 10-15 min of ischemia [33,34,36]. Such a brief period of ischemia does not lead to irreversible myocardial damage, but upon reperfusion, recovery of contractile function is delayed ("stunned myocardium") [5,7,[41][42][43][44][45]. In the following paragraphs we present some data characterizing the SR Ca 2+ pump function in stunned myocardium.…”
Section: Alterations In the Sr Ca 2 + Pump Function In The Ischemic Amentioning
confidence: 99%
“…The decrease in SR Ca 2÷ uptake rate usually appears after 10-15 min of ischemia [33,34,36]. Such a brief period of ischemia does not lead to irreversible myocardial damage, but upon reperfusion, recovery of contractile function is delayed ("stunned myocardium") [5,7,[41][42][43][44][45]. In the following paragraphs we present some data characterizing the SR Ca 2+ pump function in stunned myocardium.…”
Section: Alterations In the Sr Ca 2 + Pump Function In The Ischemic Amentioning
confidence: 99%
“…Heat shock proteins (HSPs) are a group of highly conserved proteins that can be stimulated by heat shock and other environmental and pathophysiological stresses [23][24][25][26][27][28][29]. Also glucose regulated proteins (GRPs), ubiquitin, c~13-crystalline and heme oxygenase [24][25][26][28][29][30][31][32][33] are included in the group of HSPs.…”
Section: Introductionmentioning
confidence: 99%
“…Also glucose regulated proteins (GRPs), ubiquitin, c~13-crystalline and heme oxygenase [24][25][26][28][29][30][31][32][33] are included in the group of HSPs. These proteins participate in cellular defense mechanisms and enable cells to survive and recover from stressful conditions [23,26,27,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that brief periods of ischemia are strong inducers of gene expression. [3][4][5][6] However, a link between increased transcription of a mRNA species and adaptational changes has not been established. 7) In the present study, we employed differential display reverse transcription-polymerase chain reaction (DDRT-PCR) to show the gene expression pattern in rat heart six weeks after MI.…”
mentioning
confidence: 99%